Malaysia going greens: a study on community commitment towards a greener urban living environment - Ismail, Nor Atiah; Nangkula, Utaberta; Ismail, Sumarni; Mohd Yunus, Mohd Yazid (American-Eurasian Network for Scientific Information, 2015)
A residential landscape is one expression of the intrinsic and cognitive values of a relationship between humans and their environment. Experiential and phenomenological landscapes are established when people shape their living environment; in turn they are shaped and constructed by this living environment. In Malaysia, the rural cultural landscape is one example of the above phenomenon, creating a sustainable living experience. Rural villagers are communally involved in the establishment of place identity, developing sense of place and sense of belonging towards their living space. In contrast, urban residents of low cost housing in Malaysia experience a different situation. Their physical living setting is pre-constructed and unsustainable, without them getting involved. This includes not only the houses, but also the public landscape surrounding residential areas. These “prepared” living settings present different living phenomena compared to the rural cultural landscape. Landscape alteration is one of the responses to the feelings of “outsideness” during the postoccupancy period. It is known that in some places in Kuala Lumpur residents removed the planted trees in the public landscape areas and replaced them with their desired species. They intruded into the public spaces adjacent to their homes to create small orchards, herb gardens and construct personal carports and storage barns. Overall, the pre-constructed landscape has changed significantly during this period. The discussion will be based on the qualitative research findings. It will contribute to the understanding of how the cultural landscape in an urban residential area provides a means of bonding people and place while creating a sustainable living ambience. This will contribute to awareness among the policy makers, landscape architects and developers of the importance of developing a sustainable, conducive and responsive urban living environment for the community.